Multiple roles of GluN2B-containing NMDA receptors in synaptic plasticity in juvenile hippocampus. (January 2017) - France, Grace; Fernández-Fernández, Diego; Burnell, Erica S.; Irvine, Mark W.; Monaghan, Daniel T.; Jane, David E.; Bortolotto, Zuner A.; Collingridge, Graham L.; Volianskis, Arturas
Abstract: In the CA1 area of the hippocampus N -methyl-d -aspartate receptors (NMDARs) mediate the induction of long-term depression (LTD), short-term potentiation (STP) and long-term potentiation (LTP). All of these forms of synaptic plasticity can be readily studied in juvenile hippocampal slices but the involvement of particular NMDAR subunits in the induction of these different forms of synaptic plasticity is currently unclear. Here, using NVP-AAM077, Ro 25-6981 and UBP145 to target GluN2A-, 2B- and 2D-containing NMDARs respectively, we show that GluN2B-containing NMDARs (GluN2B) are involved in the induction of LTD, STP and LTP in slices prepared from P14 rat hippocampus. A concentration of Ro (1 μM) that selectively blocks GluN2B-containing diheteromers is able to block LTD. It also inhibits a component of STP without affecting LTP. A higher concentration of Ro (10 μM), that also inhibits GluN2A/B triheteromers, blocks LTP. UBP145 selectively inhibits the Ro-sensitive component of STP whereas NVP inhibits LTP. These data are consistent with a role of GluN2B diheretomers in LTD, a role of both GluN2B- and GluN2D- containing NMDARs in STP and a role of GluN2A/B triheteromers in LTP. This article is part of the Special Issue entitled 'Ionotropic glutamate receptors'. Highlights: Inhibition of GluN2Bs in P14 is sufficient for blockade of NMDAR-LTD. GluN2A and GluN2D subunits are not required for the induction of LTD. Induction of STP involves GluN2B and GluN2D subunits. Induction of LTP depends on GluN2A/2B triheteromers.